Effect of pituitary gland doses on artificial propagation of Guchibaim, Mastacembelus pancalus (Hamilton) - Rahman, MM; Miah, MI; Hasan, KR; Farid, SM (Journal of the Bangladesh Agricultural University, 2012)
Artificial propagation of Mastacembelus pancalus was conducted in order to determine the optimum dose of pituitary gland (PG) hormone at the hatchery of the Field Laboratory Complex, Faculty of Fisheries, Bangladesh Agricultural University, Mymensingh. The present study consisted of two trials and each trial had four treatments (T1, T2, T3 and T4, respectively) with three replications of each. In the experiment single dose and double dose had been used for T1, T2, T3 and T4, respectively to evaluate the efficiency on ovulation rate, fertilization rate, and hatching rate of M. pancalus eggs. The hatchlings were reared in aquarium up to 30 days and survival rate was determined. Treatment-3 (T3) of double dose (170mg PG kg-1 and 60mg PG kg-1 body weight of fish for female and male respectively) showed better results in terms of ovulation rate (90.03±2.56%), fertilization rate (90±0.81%), hatching rate (80±1.84%), and survival rate (40.00±3.19%) was recorded than other treatments of single and double dose. The water temperature was recorded 27 to 31°C. In the present study, treatment-3 (T3 in double dose) was the best findings in terms of ovulation rate, fertilization rate, and hatching rate which can be used in artificial propagation of M. pancalus for the development of hatchery production. May and June are the suitable months for artificial propagation of the said species. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11045 J. Bangladesh Agril. Univ. 9(2): 305310, 2011